1996
DOI: 10.1177/026988119601000402
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of basal and stress-induced dopamine release in the cerebral cortex and nucleus accumbens of freely moving rats by the neurosteroid allopregnanolone

Abstract: The neurosteroid allopregnanolone is a potent and efficacious modulator of γ-aminobutyric acid (GABA) type A receptors. The effects of intracerebroventricular injection of allopregnanolone (5 to 15 μg in 5 μl) on basal and stress-induced changes in the extracellular concentrations of dopamine were investigated by microdialysis in various brain areas of freely moving rats and compared with those of the benzodiazepine midazolam (1 to 10 μg in 5 μl). Allopregnanolone reduced (by a maximum of 65 to 75%) basal dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 33 publications
3
43
0
1
Order By: Relevance
“…A recent clinical report also demonstrated that the ALLO concentrations stemming from 30 mg progesterone, but not 0, 60 or 200 mg were associated with enhanced negative mood scores in postmenopausal women [1]. Lastly, administration of 100 pmol ALLO into the lateral ventricle was found to elevate extracellular dopamine content in the NAc [32] whereas 45 nmol ALLO suppressed this measure [24]. Notably, ALLO's peak effect (50 ng; equivalent to 150 pmol) on bout micro-architecture in the present study closely resembled the concentration and route of ALLO administration (100 pmol; ICV) that led to enhanced dopamine content in the NAc.…”
Section: Discussionmentioning
confidence: 94%
“…A recent clinical report also demonstrated that the ALLO concentrations stemming from 30 mg progesterone, but not 0, 60 or 200 mg were associated with enhanced negative mood scores in postmenopausal women [1]. Lastly, administration of 100 pmol ALLO into the lateral ventricle was found to elevate extracellular dopamine content in the NAc [32] whereas 45 nmol ALLO suppressed this measure [24]. Notably, ALLO's peak effect (50 ng; equivalent to 150 pmol) on bout micro-architecture in the present study closely resembled the concentration and route of ALLO administration (100 pmol; ICV) that led to enhanced dopamine content in the NAc.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, allopregnanolone decreases stress-induced dopamine release in rodent cerebral cortex and nucleus accumbens (Motzo et al, 1996) and influences dopamine-mediated rodent behaviors (Khisti et al, 2002). The GABAergic neuroactive steroid 3a,21-dihydroxy-5a-pregnan-20-one (THDOC) also decreases stress-induced prefrontal cortical dopamine release (Grobin et al, 1992).…”
Section: Discussion Olanzapine and Clozapine Effects On Cerebral Cortmentioning
confidence: 99%
“…Olanzapine is known to block dopamine receptors with relatively weaker potency and the blockade of receptors, other than D 2 , is thought to be responsible for its atypical antipsychotic profile (Bymaster et al, 1999). Moreover, ALLO represents the most potent positive modulator of GABA A receptor and is known to diminish basal and stress-induced dopaminergic transmission in the brain by its action on GABA A receptors (Motzo et al, 1996). Our observation that bicuculline pretreatment antagonized the effects of olanzapine on CAR-and apomorphineinduced climbing behaviors suggests that the antipsychoticlike action of olanzapine could be mediated via activation of GABA A receptors.…”
Section: Discussionmentioning
confidence: 66%
“…Our observation that bicuculline pretreatment antagonized the effects of olanzapine on CAR-and apomorphineinduced climbing behaviors suggests that the antipsychoticlike action of olanzapine could be mediated via activation of GABA A receptors. Consequently it may be speculated that the influence of ALLO on dopaminergic neurotransmission might be mediated via GABA A receptors (Motzo et al, 1996;Khisti et al, 2002) perhaps through modulation of intracellular signaling mechanisms like protein kinase C (PKC) (Brunig et al, 1999;Brussard et al, 2000;Liu et al, 2000). That the activation or inhibition of PKC increases or decreases, respectively, dopamine release in striatum has already been demonstrated (Gimbalvo, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation